FRI0359 KRT77 DELETIONS IN FAMILIAL INFLAMMATORY BOWEL DISEASE MAY OFFER A NOVEL LINK TO FAMILIAL SPONDYLOARTHROPATHY. (June 2019) - Julià, Antonio; Cuthbert, Richard; Glueck, Anton; Gisbert, Javier; Domènech, Eugeni; Lasanta, Maria Lopez; Palau, Núria; Marzo-Ortega, Helena; McGonagle, Dennis; Marsal, Sara
Abstract : Background: Inflammatory bowel disease, either clinical or subclinical is a cardinal pathological process that is central to the spondyloarthropathy (SpA) category of disease that also includes psoriasis, psoriatic arthritis, uveitis and ankylosing spondylitis. Objectives: To look for novel genes in familial SpA in large multcase families using a whole genome sequencing approach. Methods: We used Whole Genome Sequencing to screen SpA family members with different disease manifestations. We screened 5 multicase SpA families (up to 8 members) with different disease manifestations. Results: We found a 1.5MB deletion of the KRT77 gene in 3 of 7 families that segregated with SpA phenotype. Given that KRT77 is a barrier protein and given that tagging SNPs from GWAS studies do not cover the region, and given that both IBD and psoriasis are associated with barrier defects, we looked for an association with KRT77 deletion in 1, 000 cases of Psoriasis, 1, 000 Crohn's disease (CD) and 1, 001 healthy controls. Deletion genotyping was performed using TaqMan RealTime-PCR assays. The deletion genotype frequencies in controls did not deviate from Hardy-Weinberg Equilibrium (p > .1). We found an association between KRT77 deletion and CD risk (p = 0.03) and also a putative association with pustular psoriasis (p < 0.05). We also demonstrated that the KRT77 protein is expressed in the intestinal lumen and Peyers Patches in addition to the know skin expression. Conclusion: Given the strong association between SpA and subclinical gut inflammation and barrier defects in IBD these findings suggest that KRT77 heterozygous deletions with dysregulated gut permeability may play a role in IBD and the wider SpA phenotype. Acknowledgement: We would like to thank the clinical researchers and patients participating in the IMID Consortium for their collaboration Disclosure of Interests: Antonio Julià: None declared, Richard Cuthbert: None declared, Anton Glueck: None declared, Javier Gisbert: None declared, Eugeni Domènech: None declared, Maria Lopez Lasanta: None declared, Núria Palau: None declared, Helena Marzo-Ortega Grant/research support from: Janssen, Novartis and Pfizer, Consultant for: AbbVie, Celgene, Janssen, Eli-Lilly, Novartis and UCB, Speakers bureau: AbbVie, Celgene, Janssen, Eli-Lilly, Novartis and UCB, Dennis McGonagle Consultant for: Lilly, Novartis UCB, Speakers bureau: Lilly, Novartis UCB, Sara Marsal: None declared